Uso de biodigestor anaeróbio no tratamento de resíduo orgânico de restaurante - Granzotto, Fabiane (2016)
The generation of local solid waste has increased every year in Brazil. The largest portion of this waste is organic material. Organic waste generated in restaurants in the preparation of meals, as much as in the leftovers on the plates plays an important role in the composition of this type of waste and needs to be properly allocated. In the present study, the generation of biogas and bio compounds in the use of restaurant organic waste was evaluated, in an anaerobic digester. To achieve this, an anaerobic reactor of 120 L was used, which was operated and monitored from August 2015 to April 2016. The anaerobic digestion was conducted at mesophilic temperature close to 30 °C and at different hydraulic retention times of 30 and 60 days. Initially, the pH of the affluent varied from 4.8 to 6.4 performing in most cases as acid; therefore it was necessary to correct the incoming biomass with NaOH. The major physic-chemical factors which influenced in the process and the biogas composition (CH4 and CO2) were evaluated. The stable phase was identified and the removal efficiency of main physic-chemical parameters was verified during this stable period. The pH of the effluent on stage II varied from 6.2 to 7.3. The average COD removal was 95 %, BOD5, 93%, O&G, 86 %, ST, 51 %, SS, 92 % and STV, 76 %. The percentage of CH4 in phase II was 60 % and 40 % of CO2. During the period in which the digester was operated and evaluated the amount of 203 kg of restaurant organic waste was properly allocated, 633 L of water were used and 830 L of bio compounds were generated. The total volume of biogas followed in March and April 2016 was 3311.72 L and the estimated total volume for methane was 2123.24 L, in a range of daily variation biogas production from March to April of 41.2 L to 80.0 L. The study found that with the acclimatization of microorganisms was possible to obtain positive percentage of methane generation indicating that anaerobic digestion, for this type of waste used, is viable and it has good potential for use, in addition of generating gases production with potential energy and sludge with potential use in fertilization.